DINTER projects: Contribution to the expansion of National Graduate System in Brazil - Flávia Melissa Souza Moraes; Maria Rosa Chitolina Schetinger (Arizona State University, 2019)
This article investigates the interinstitutional PhD projects' (DINTER) influence on the National Graduate System expansion in Brazil. These projects are a graduate system flexibilization in which a graduate institution named the promoter offers its stricto sensucourse to another institution, the receptor. First, we analyzed the approved projects on three different calls for proposals, CAPES-SETEC and New Frontiers, that last from 2007 to 2009, and the nº 13 call, published on 2011. Second, from 2009 to 2016, we checked the receptor institutions that had established their own courses in the same field of the previously approved projects. To corroborate the influence relation, it was observed the data annually informed by the promoter institution during the DINTER effectiveness, and the one communicated by the receptor institution after developing its own course. The results showed a direct contribution of these projects to the faculty qualification when conceiving new graduate courses, which justifies the public policy under analysis.